Phenylhydrazine-induced haemolysis disturbed iron pool homeostasis and activated expression pattern of FPN1 in the intestine of grass carp (Ctenopharyngodon idella) - Huang, Xiaoman; Chen, Hong; Tu, Chenming; Zhang, Linpeng; Liu, Lihan; Lin, Li; Qin, Zhendong; Zhan, Fanbin (Aquaculture and fisheries, 2025)
As the only molecule that can transport iron to the cell exterior, the ferroportin 1 (FPN1) plays a key role in regulating the homeostasis of the iron ion. However, the function of FPN1 in teleost is remains unclear. In this study, the fpn1 gene was cloned from grass carp and its characteristics were studied. The results showed that grass carp Fpn1 protein contains eight transmembrane domains, which are similar to the amino acid sequences of different species. The tissue distribution of fpn1 was investigated by quantitative real-time PCR (qRT-PCR), which showed that the expression of fpn1 was the highest in the liver, followed by the spleen and muscle. Secondly, the haemolysis model of grass carp was established by the injection of phenylhydrazine (PHZ), and the effect of Fpn1 on the intestine in during haemolysis was explored. The determination data revealed that the PHZ-induced haemolysis increased the number of goblet cells in intestinal, as well as malondialdehyde (Mda), decreased glutathione peroxidase 4 (Gpx4) content in foregut. The result of tissue immunofluorescence assay showed that the PHZ-induced haemolysis modulated the expression of iron metabolism related genes, including Fpn1 and Tfr1 (transferrin receptor 1) in the intestine. Further determination data suggested that the iron deposition and apoptosis were higher in PHZ treatment group than that of the group. Taken together, the PHZ-induced haemolysis destroyed the iron homeostasis in intestinal and caused oxidative damage, the data of this study lays a foundation for the study of the mechanisms of intestinal iron homeostasis and provides a theoretical basis for understanding intestinal healthy.